ФОРМУВАННЯ КУЛЬТУРИ ПРОФЕСІЙНОГО СПІЛКУВАННЯ ЯК СКЛАДОВОЇ ПРОФЕСІЙНОЇ КУЛЬТУРИ МАЙБУТНІХ ФАХІВЦІВ-АГРАРІЇВ (Педагогіка вищої та середньої школи, 2008)
The article is dedicated to the question of “professional culture ” and to analyses of ways of professional culture formation of agrarian students by means of foreign languages.